Peningkatan Minat Belajar Menggunakan Model Pembelajaran Team Games Tournament Pada Siswa Sekolah Dasar - Martopo, Martopo (Faculty Of Education, 2024)
This research aims to increase students' interest in learning science in class III through the Team Games Tournament (TGT) model at SD Negeri 007 Rokan IV Koto. This research was motivated by the low interest in learning of class III students for the 2023/2024 academic year, consisting of 13 students consisting of 6 male students and 7 female students. This research was conducted in two cycles, each cycle consisting of two meetings. Data collection in this research used instruments in the form of questionnaires, observation sheets on students' learning interests and interview sheets. Based on the results of data analysis, it can be seen that there is an increase in students' interest in learning in science subjects. Before the action, the completeness of students' learning interest results only reached 36.77%. Then in cycle I, meeting 1 increased to 40.38%, in cycle I, meeting 2, it increased to 45.42%, in cycle II, meeting 1, it increased to 56.36%, in cycle II, meeting 2, it increased again to 76.56%. Thus, it can be concluded that using the Team Games Tournament (TGT) model can increase elementary school students' interest in learning.